Myocardial tissue phase mapping reveals impaired myocardial tissue velocities in obesity - Rider, O; Ajufo, E; Ali, M; Petersen, SE; Nethononda, R; Francis, J; Neubauer, S (Springer Science+Business Media Dordrecht, 2014)
Although obesity is linked to heart failure on a population level, not all obese subjects develop cardiac failure. As a result, identifying obese subjects with subclinical changes in myocardial velocities may enable earlier detection of those susceptible to developing overt heart failure. As echocardiography is limited in obesity due to limited acoustic window, we used phase contrast magnetic resonance imaging to assess myocardial velocities in obese and normal weight subjects. Normal weight (BMI 23 ± 3; n = 40) and obese subjects (BMI 37 ± 7; n = 59) without identifiable cardiovascular risk factors underwent MRI (1.5 Tesla) to determine left ventricular myocardial velocities using phase contrast tissue phase mapping. Systolic function was not different between normal and obese subjects (LVEF 67 ± 5 vs 68 ± 4, p = 0.22). However, obesity was associated with significantly impaired peak radial and longitudinal diastolic myocardial velocity (by 13 and 19 % respectively, both p < 0.001). In addition time-to-peak longitudinal diastolic velocity was delayed in obesity (by 39 ms, p < 0.001). In addition, peak longitudinal diastolic strain was 20 % lower in obesity (p = 0.015) and time-to-peak longitudinal diastolic strain rate significantly delayed in obesity (by 92 ms, p < 0.001).Although peak radial systolic velocity was similar between obese and normal weight subjects (p = 0.14) peak longitudinal systolic velocity was 7 % lower in the obese cohort (p = 0.02). In obesity without co-morbidities, tissue phase mapping has shown subclinical changes in systolic and diastolic function. Given the link between obesity and heart failure, early detection of changes may become clinically important to prevent disease progression. © 2014, Springer Science+Business Media Dordrecht.